2004
DOI: 10.1074/jbc.m405502200
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Ester Treatment of K562 Cells Regulates the Transcriptional Activity of AML1c through Phosphorylation

Abstract: We find that phorbol ester (PE) treatment of K562 cells greatly stimulates promoters (T cell receptor ␤, myeloperoxidase, macrophage colony-stimulating factor receptor, and granulocyte macrophage colony-stimulating factor receptor) containing AML1 transcription factor binding sites. This stimulation of AML1c transcriptional activity is mediated by direct phosphorylation of the AML1c molecule on multiple phosphorylation sites. Eleven AML1c (S/T)P sites in the transcriptional activating domain are phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 34 publications
6
43
0
Order By: Relevance
“…Mutation of Ser104, corresponding to Ser125 on the murine Runx2 type II isoform, to both glycine and glutamic acid inhibited Runx2 transactivation of an OCN-promoter-driven reporter gene (Wee et al, 2002). These results are consistent with our observations for Runx2-mediated differentiation, but contradict reports that mutation of Runx1/AML1c Ser94, analogous to Runx2-Ser125, had no effect on transcriptional activity (Zhang et al, 2004). Wee and colleagues also reported that the phosphorylation state of Ser451, corresponding to Ser472 on the murine Runx2 type II isoform, has a crucial role in the transcriptional activity of Runx2 (Wee et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mutation of Ser104, corresponding to Ser125 on the murine Runx2 type II isoform, to both glycine and glutamic acid inhibited Runx2 transactivation of an OCN-promoter-driven reporter gene (Wee et al, 2002). These results are consistent with our observations for Runx2-mediated differentiation, but contradict reports that mutation of Runx1/AML1c Ser94, analogous to Runx2-Ser125, had no effect on transcriptional activity (Zhang et al, 2004). Wee and colleagues also reported that the phosphorylation state of Ser451, corresponding to Ser472 on the murine Runx2 type II isoform, has a crucial role in the transcriptional activity of Runx2 (Wee et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…and A.J.G., unpublished data). Similarly, mutation of Runx1/AML1c Ser424, corresponding to Runx2 type II Ser472, did not alter transcriptional activity of this runt-domain protein family member (Zhang et al, 2004). Overall, it is evident that disparities exist in the phosphorylation pattern of Runx protein family members, suggesting that the phosphorylation state of Ser125 and Ser472 might be isoform specific, cell-type-specific, or regulated by independent signaling pathways.…”
Section: Discussionmentioning
confidence: 88%
“…Autoradiography shows that a constitutive phosphorylation of AML1 occurs in the presence or the absence of TPO. This result is consistent with previous observations by Tanaka et al 30 and Zhang et al 31 that TPO induced 32 P incorporation in the slower migrating band specifically. This result demonstrates that the upper band of AML1 represents a phosphorylated form of AML1 and that TPO induces AML1 phosphorylation.…”
Section: Tpo Induces Erk-dependent Phosphorylation Of Aml1supporting
confidence: 94%
“…The regulation of AML1 functions through signal transduction pathways has been investigated, and, by overexpression experiments, AML1 has been shown to be phosphorylated by ERK. 30,31 ERK-dependent phosphorylation enhances the transcriptional activity of AML1, and mutations of the phosphorylation sites reduce the transforming activity of AML1 in the fibroblast cell line. 30 These results indicate a possible link between TPO, ERK, AML1, and megakaryopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…The ⌬260-280 and PY motifs were specifically targeted in these experiments because the former contains several proline-directed serine and threonine residues reported as ERK phosphorylation targets, whereas the latter resides within the transactivation domain of RUNX1 and is known to mediate protein-protein interaction. 22,36,37 We further examined the ability of these RUNX1 variants in inducing p300 phosphorylation and found that all 3 phosphorylationdefective RUNX1 variants were unable to promote p300 phosphorylation in the presence of PEBP2-␤ ( Figure 2D bottom panel). These observations are consistent with the notion that phosphorylation of RUNX1 and p300 are coupled events.…”
Section: Delineation Of Runx1 Protein Domains Essential For Pebp2-␤-imentioning
confidence: 99%